Colorectal Cancer, Socioeconomic Distribution and Behavior: A Comparative Analysis of Urban and Rural Counties in the USA (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Colorectal cancer (CRC) ranks second for all cancer related deaths among men and women together and third for either sex when considered separately. Disparities exist in CRC incidence and mortality between rural and urban counties in the USA. This study sought to explore socioeconomic and behavioral factors that may partly explain these observed differences.Methods: Using educational and income levels as measures of socioeconomic status (SES), and average alcohol consumption and smoking frequency as behavioral factors, data from the Behavioral Risk Factor Surveillance System (BRFSS) and the Surveillance, Epidemiology, and End Results (SEER) program for analysis were coupled.Results: Results showed statistically significant inequalities for CRC incidence (t = 2.678, p = 0.010) and mortality (t = 2.567, p = 0.013), as well as socioeconomic (i.e., poverty; t = 5.644, p < 0.001) and behavioral (i.e., smoking; t = 2.885, p = 0.006) factors between selected rural and urban counties. Regression analysis for colorectal cancer incidence and mortality rates at the rural, urban, and national levels yielded relative impacts of smoking frequency, alcohol consumption, and educational level.Conclusions: Health policies aimed at reducing disparities between rural and urban populations in the USA must therefore adequately address SES and behavioral factors.Key words: colorectal cancer, rural health, social determinants of health, health behavior